Respuesta :

okay so we need to solve for x.

--

FIRST STEP:  12x^2+5x-4=12^2x+6 would turn into x2 + 5x - 4 = 2x + 6 so it'd have equal bases.

SECOND STEP: move any number with "x" in it to the left side. it ends up as  x2 + 3x - 4 = 6

THEN, we use the AC method to eliminate any unnecessary numbers.

you should end up with ( x - 2) (x + 5) = 0

SO, the answer is your third option. ( x = 2, x = -5)

Answer:

x=-5&x=2

Step-by-step explanation:

Since the bases on both sides of the equation are the same, they will cancel each other leaving the exponents

x²+5x-4 = 2x + 6

Collect like terms

x²+5x-2x-4-6=0

x²+3x-10=0

The highest power is 2 , so factorize

x²+5x-2x-10=0

x(x+5)-2(x+5)=0

(x+5)(x-2)=0

x = -5 or x = 2

Check

When x = -5

-5²+3*-5-10=0

25-15-10 =0

0=0

:.x=-5

When x=2

2²+3*2-10=0

4+6-10=0

0=0